Planning for retail resilience: Comparing Edmonton and Portland. (October 2016) - Rao, Fujie; Summers, Robert J.
Abstract: Commercial retail areas within cities have traditionally not only satisfied the demands for various goods and services, but have also contributed to elements of community sustainability and livability as a form of public good. Since the end of World War II, innovations in retail formats have occurred as retailers seek to maximize their financial efficiency. However, this often has consequences for community sustainability and livability. This research employs resilience theory to examine how cities have coped with retail innovations through a comparative case study of Edmonton (Alberta, Canada) and Portland (Oregon, USA). Through historical document review and interviews with senior planners in both cities, it is found that adaptive retail management which emphasize principles over visions, which feature an active, informed, and highly organized public and a polycentric planning system encouraging planning diversity and consensus building can contribute to more resilient retail outcomes that preserve a broader range of retail and public functions. Highlights: We compare the retail planning history of metropolitan regions of Edmonton & Portland. The focus is upon the contributions of retail to both market and non-market contributions. Portland's adaptive approach was more effective in balancing market efficiency and non-market contributions. Key elements of an adaptive approach include an active citizenry, principle focused planning, and polycentric decision making.